Health and medical services in times of armed conflict: draft resolution proposed by the delegations of Australia, Belgium, Bulgaria, Cameroon, Central African Republic, Congo, Croatia, Denmark, Finland, Gambia, Iceland, Kenya, Lebanon, Maldives, Norway, Rwanda, Swaziland，Sweden, Switzerland, Thailand, Tonga, and Trinidad and Tobago - World Health Assembly, 46 (World Health Organization, 1993)
(Agenda item 31.1)